Six ways to get a grip on computer vision syndrome in medical school examinations - Golrokhian-Sani, Amir-Ali; Morcos, Maya; Gottlieb, Chloe (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2025)
Computer Vision Syndrome is a group of vision symptoms related to screen use, which is a growing point of concern as screens become more integrated into daily life. Medical students are hit particularly hard by this, as they report substantial levels of screen use. While screens are practically necessary in medical education, there are areas of harm reduction that have yet to be addressed. Medical exams are particularly hostile to eye health, as students have to stare at screens for prolonged periods, making them ideal subjects for eye protection and education interventions. Some steps that examiners can take to encourage positive habits in their students are to extend exams with spaces for five-minute breaks or according to the 20-20-20 Rule, encourage an area of alternate fixation for eye breaks, add audio cues signalling breaks, educate about environmental and postural modifications to improve eye health, allow lubricating drops in exams, and modify exams to decrease suspicion of academic misconduct.